Avestan hymn to mithra ; translated by Ilya Greshevitch (London, 1967)
The Avestan Hymn to Mithra, written in the fifth century BC, is the one extensive, ancient literary record of the attributes, companions and cult of the Iranian god whose worship spread, five or six centuries later, as far as Britain. Dr Gershevitch here